Lutheran Secularism as a Challenge for Constructive Theology: A Swedish Perspective, a Foucauldian Proposal. Issue 3 (4th September 2017) - Martinson, Mattias
Abstract: In this article the Swedish Lutheran heritage is discussed in relation to its historical connections with secularism. The question is raised whether and how constructive and liberating Lutheran theology can be developed under such conditions. In order to deal with this problem, Michel Foucault's late philosophy of truth and subjectivity is discussed. A proposition is made for a constructive theology that does not retreat from secularism but is critically involved in the secular through an emphasized confidence in God.